Learning from Others: Literacy Perspectives of Middle-School English Teachers - Cynthia A. Lassonde (Networks: An Online Journal for Teacher Research, 2002)
At the center of this interview-based study, middle-school English teachers talk and write about their literacy development, their teaching philosophies, and their curriculum, as they reflect upon their teaching. Portraits of their perspectives of literacy emerge. Using these portraits to reflect upon teaching practices, the author suggests we can effectively examine our own educational philosophies, contributing to our efforts to become increasingly competent educators.